2018
DOI: 10.1089/rej.2018.2069
|View full text |Cite
|
Sign up to set email alerts
|

A High-Intensity Jump-Based Aquatic Exercise Program Improves Bone Mineral Density and Functional Fitness in Postmenopausal Women

Abstract: The aim of this study was to verify the effects of a high-intensity jump-based aquatic exercise (HIIAE) program on bone mass and functional fitness in postmenopausal women. We randomly assigned 25 women (65 ± 7 years) into two groups: Training group (T, n = 15) and Untrained group (Un, n = 10). The T group was submitted to 24 weeks of HIIAE program, where each session lasted for 30 minutes. The following parameters were assessed before and 6 months following the intervention: bone and physical fitness; lumbar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 37 publications
1
44
1
4
Order By: Relevance
“…BMD is reported to decrease with age, 3 but in the present study, BMD remained stable, showing just a slight nonsignificant increase over a six-year period. Moreover, none of the athletes showed any signs of osteopenia or osteoporosis in a study by Nowak et al, 8 comparing male long-distance runners and male nonathletes.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…BMD is reported to decrease with age, 3 but in the present study, BMD remained stable, showing just a slight nonsignificant increase over a six-year period. Moreover, none of the athletes showed any signs of osteopenia or osteoporosis in a study by Nowak et al, 8 comparing male long-distance runners and male nonathletes.…”
Section: Discussioncontrasting
confidence: 84%
“…It should be considered that athletes and people who engage in physical exercise have better bone mass than those who do not engage in physical exercise; this is owing to the mechanical overload on the bone, inducing the formation of osteoblasts, piezoelectric effect, and the same mechanism of traction of the muscles on the bone. 3 However, studies have shown that after a certain BMD peak is reached, there is no further improvement in bone mineralization unless there is an increase and modification of the stimulus. 12 Indeed, results of the present study show that only an increase in the stimulus leads to an improvement of BMD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nesse sentido, uma prescrição adequada de exercícios requer uma avaliação física prévia, que consiste na realização de uma bateria de testes físicos, que permitem um diagnóstico individual da capacidade funcional do praticante, bem como a identificação de suas possíveis limitações (ACSM, 2010). Em ambientes, clínico e científico, os testes de sentar e levantar, "timed up and go", e o teste de caminhada de 6 minutos, ganharam popularidade nos últimos anos e são amplamente utilizados para avaliação do desempenho neuromuscular de membros inferiores, velocidade de deslocamento com mudança de direção e aptidão cardiorrespiratória, respectivamente (Aboarrage Junior, et al, 2018;Dos Anjos, et al, 2017;Harmsen, et al, 2017;Milanovic, et al, 2013) .…”
Section: Introductionunclassified